Association behaviour and rheology of palm based emulsion using mixed sugar based emulsifiers - Ismail, Zahariah (2001)
Methyl glucose based emulsifiers such as Glucamate SSE-20 ( PEG-20 methyl glucose sesquistearate) and Glucate SS (methyl glucose sesquistearate) are widely used in the application of cosmetic products. The methyl glucoside products have excellent safety, mildness and effectiveness. Although these methyl glucosides are widely used as emulsifiers, little is known about their phase behaviour in binary and ternary systems. The phase behaviours in binary and ternary system have been studied at 80°c under visual observation by polarizing light and they were confirmed by polarization microscope. In the binary system, lamellar phases (La) were observed at the combination of 60/40, 70/30 and 80/20 of glucamate SSE-20 and glucate SS. It was identified as maltese crosses and oily streaks. When heated at 80°C, the oily streaks pattern of 70/30 took a longer time to change to isotropic phases if compared to the other ratios. This observation correlated well with yield val ue, viscosity, and thixotropy in the following order 70/30> 60/40>80/20. In the ternary system (mixed sugar based emulsifiers/water/medium chain triglycerides), the optical pattern indicated a combination of maltese crosses + oily streaks, maltese crosses and oily streaks texture alone. This system exhibited viscoelastic properties Equal ratio of medium chain triglycerides and water (1/1) were emulsified with 5% w/w of mixed non ionic sugar-based surfactants with various hydrophilic-lipophilic balance val ues (HLBs). The HLB numbers ranged from 6.6 to 15.0. The effect of H LB and with and without hydrocolloids on stability, particle size droplet and rheological properties of the resulting emulsions were studied. The presence of hydrocolloids in the emulsion system dramatically lowers the interfacial tension and thus increased interparticle attraction, weak van der Waals and increased steric repulsion to stabilize the system. The systems show increasing viscosity, yield value, critical stress and exhibit viscoelastic properties The ratio of bound water and bulk water in emulsion system is determined by thermogravimetry. Shifting the ratio of bound water and bulk water may result in regulated release of water, a principle that can be used to produce cream or lotion with controlled release of moisture